Pedestrian Infrastructure Quality of Service In Urban Neighborhood: A Case Study in Wangsa Maju, Kuala Lumpur, Malaysia: A Case Study in Wangsa Maju, Kuala Lumpur, Malaysia - Ida Shaheera Bakhtiar; Safizahanin Mokhtar; Muhammad Zaly Shah Hussein (Civil and Sustainable Urban Engineering, 2022)
The effectiveness of security and accessibility to all facilities supplied in the neighborhood area was evaluated using the Pedestrian Infrastructure Quality of Service methodology. The method is known as a "mix of land uses to test pedestrian connectivity," and it encompasses land use and connectivity within a 400-meter walking radius, as indicated on the map. According to the findings, 28% of pedestrians in the age range of 25–34 years old were eager to walk in a neighborhood with good pedestrian infrastructure and a safe environment for walking. The elderly were less willing to walk because of the lack of pedestrian infrastructure, which prevented people from using walking as a mode of transportation. Professionals, who accounted for 45.6 % of all responses, favored increased provision for pedestrians in the neighborhood area to encourage more people to walk instead of driving private vehicles.